Studi Deskriptif Manajemen Konflik Pada Studi Psikososial Mengenai Gaya Resolusi Konflik Pasangan Suami-Istri Berumur 20-40 Tahun di Gereja Kristen Indonesia Maulana Yusuf Bandung - Levitania, Lydia Fransiska (Manajemen Bisnis Kompetensi, 2017)
Abstract This study was conducted to describe the conflict resolution styles on married couples aged 20-40 years in the church GKI Maulana Yusuf Bandung. The sample in thisstudy consisted of 24 couples. Measurement instrument that used in this study was a translation of 16 items of conflict resolution styles inventory (CRSI) which has been prepared by Kurdek (1994). Based on the validation process, all items were proven to be valid. Meanwhile, the reliability testing shown the items on the positive problem solving and conflict engagement styles were relatively high, while the withdrawal and compliance styles were relatively moderate in reliability. The result of this study shown that in the individual context; 83.3% of the respondents using positive problem solving style, 8.3% using withdrawal style, 6.3% using compliance style, 2.1% using the mixed type (withdrawal-compliance), and no one was using conflict engagement style. Further in the context of couples; 79.1% couples have a combination of constructive conflict resolution styles, while 20.9% couples have a combination of destructive conflict resolution style. This study suggested that the couple with a positive problem solving style should maintain that type, while the couple with a withdrawal, compliance, and the mixture styles should be trained to develop skills to resolve conflicts. This study also suggested that the Pastor and the church could make a specific program about conflict resolution in marriage life. Keywords: conflict resolution styles, marriage couples, positive problem solving, withdrawal, mixture styles.